Measles outbreak investigation, Greater Francistown District, Botswana, 2023 - Utlwanang Modise; Tshepang Carter Ntsose; Gotsileene Monamodi; Olerile Mosupiemeng; Boitumelo Solomon; Boitshwarelo Masunda; Onkabetse Wilson; Gorata Baraedi; Dominique Mayenzanisi; Samuel Kolane; Nesredin Jami Oumer; Uzoma Ogbonna (Journal of Interventional Epidemiology and Public Health)
Introduction: Measles causes significant childhood morbidity and mortality worldwide. Botswana has targeted measles for elimination. On January 7 2023, the Greater Francistown district health management team was informed of a suspected measles outbreak. We investigated the outbreak to verify the diagnosis, describe the epidemiological characteristics of cases and institute control measures.